Transformations of Entrepreneurial Competence in Activities - Genute Gedviliene; Virginija Bortkeviciene (European Scientific Journal, ESJ, 2016)
Scientific literature revealed entrepreneurship as quite a complex and multifaceted concept which combines different scientific disciplines and may be expressed through them. Entrepreneurship is a topic of educational and economic interest at the present time and is described as a creative and innovative response to environments, which can be and can occur in different social environment: in business, in education, social work, and industry etc. The question is how to measure what determines the entrepreneurship in activities? How entrepreneurial competence is experienced and how entrepreneurial knowledge transformations are going into activities and how entrepreneurial knowledge is acquired before the onset of the action? The purpose of this paper is to identify how entrepreneurial competence is experienced and what determines manifestation of entrepreneurial competence in activities. Research methodology. A phenomenographic research approach was adopted and semi-structural interviews with entrepreneurs identified as the most appropriate data collection tool. Findings. The research data revealed the ways that entrepreneurial competence is experienced in activities and the ways how this competence transforms into activities: through theoretical knowledge or through practical knowing. Implications. The identified categories of descriptions in this research could support a learning process: what kind of learning forms we need seeking a better understanding about entrepreneurial competence and a better use of entrepreneurial competence while this competence transforms into activities.